Management of Fusarium rot in small cardamom - Dhanya et al, M K (Indian Journal of Plant Protection, 2018)
Experiments on the management of Fusarium rot in small cardamom caused by Fusarium oxysporum Schlecht were conducted to fnd out effcacies of fungicides and biocontrol agents during summer months (February-May) of 2014 and 2015 in three farmers’ felds located at two different panchayats of Idukki district in Kerala. Four fungicides and three combinations of biocontrol agents were evaluated for their effcacy in hotspot areas of the disease. The fungicides tested in this experiment include moderatley toxic (blue labelled) chemicals (Oral LD 50: 501-5000 mg) like hexaconazole, a combination product of captan and hexaconazole, ﬂusilazole and a green labelled (Oral LD 50: more than 5000 mg) carbendazim. Biocontrol agents such as Pseudomonas ﬂuorescens along with Arbuscular mycorrhizhal fungi (AMF) and Trichoderma viride, sole application of P. ﬂuorescens in cowdung slurry as well as combined application of plant growth promoting rhizobacteria (PGPR II) with AMF and T. viride were evaluated in the feld experiments. Results of the pooled data of this experiment on disease severity (Per cent Disease Index), capsule yield and beneft cost ratio showed that P. ﬂuorescens in cowdung slurry was the best management practice against Fusarium rot of cardamom followed by combined application of P. ﬂuorescens with AMF and T. viride as well as the combination product of captan + hexaconazole.